Towards an inventory of Mexican tardigrades (Tardigrada): a survey on the diversity of moss tardigrades with an emphasis in conifer forests from the Valley of Mexico Basin - Alba Dueñas-Cedillo; Ismael Venegas; Jazmín García-Román; Enrique Jurado; Gerardo Cuellar-Rodríguez; Gabriel A. Villegas-Guzmán; Carlos Fabián Vargas-Mendoza; Enrico A. Ruiz; Francisco Armendáriz-Toledano (Check List, 2024)
From a large-scale sampling of limnoterrestrial tardigrades in the Valley of Mexico Basin, in the Huasteca Potosina, and Monarch Butterﬂy Sanctuary, Mexico, we develop an initial species list and determine the type of vegetation and substrates for most sampled species. In total 160 moss samples and over 2000 tardigrades were obtained, belonging to 17 genera, 35 putative species, one subspecies, of which eight could be accurately identiﬁed to species or subspecies, three to affinity, and 15 as morpho-species; the remaining samples were identiﬁed to genus, mainly due to the few specimens available and their preservation was not optimal. We provide novel records for one genus and two species from the country. Our estimates on ﬁve vegetation types and three substrate types indicates that our inventory is incomplete, and as many as twice the number of species may still be found in these ecosystems.